Orchards to cement: an ethnography of Jaffa's urban borderlands - Hart, JR (2020)
This thesis combines anthropological perspectives on materiality, the state, and urban planning to demonstrate how Israeli nationalism is constructed through diversity and the built environment. It illustrates how the urban borderlands of Jaffa – a mixed Jewish- Palestinian city in contemporary Israel – were transformed from were transformed from a landscape of citrus orchards populated by Palestinian bourgeois families and peasant farmers into the most densely populated neighbourhoods of Tel Aviv- Jaffa (the city was annexed by Tel Aviv in 1950). The ethnography was conducted from August 2017-March 2019 in two diverse low-income neighbourhoods of shikunim (social housing) constructed in the 1960s around remnants ofbayārāt, pre-1948 citrus farming complexes. Shikunim were central to the Israeli state building project, and bayārāt central to early 20th century Palestinian modernity, which grew through the success of the orange industry in Jaffa. Today, these neighbourhoods are marked by their ethnic diversity, which includes remaining Palestinian residents of the bayārāt, veteran Mizraḥi (Middle Eastern Jewish) and Balkan residents, new immigrants from the former Soviet Union and Ethiopia, Palestinians pushed into these neighbourhoods due to gentrification in historic Jaffa, and a growing number of middle-class Ashkenazim (European-origin Jews) as the scope of real estate development in the city expands. Through an account of how urban planning and architecture transformed the landscapes over time, the thesis depicts the relationship between territorial imagination, architectural intervention, municipal governance, built space, and the everyday navigation of residents. Arguing that these relationships have led to the multiple production of material and social borders over time, the thesis critiques the notion of urban conviviality in anthropology, sociology and urban studies, and proposes a notion of bordering to explain how persons navigate proximate difference in closed patterns. Attention to the historic transformation of these borderlands also reveals the complex relationship between material forms, memory, and contemporary social formations, as well as between quotidian state formation and its delimitations in urban space.